The role of income and gender unemployment in divorce rate among the OECD countries. (21st February 2020) - Alola, Andrew A.; Arikewuyo, Abdulgaffar O.; Akadiri, Seyi S.; Alola, Mary I.
Abstract: Economic stability is one of the most important factors to consider when examining marriage sustainability or divorce. Consequently, the current study examined the influence of income and gender unemployment on divorce in a panel study of the Organization for Economic Cooperation and Development (OECD) countries over the period 1995–2016. Empirical results show that gross domestic product per capita as a measure of income level has a negative and significant impact on the divorce rate only in the long run. In addition, findings indicated that an increase in the female unemployment level would lead to a decrease in the divorce rate, while increase in male unemployment will lead to an increase in the divorce rate in the long run. Based on the results, we infer that for individuals to sustain their romantic relationships, income sustainability is highly essential. The implication of our findings is that economic stability measured by the income level of an individual is highly essential in achieving marital stability in a romantic relationship. Hence, the study offers useful policy directions for households, governments, and other stakeholders, especially in the OECD countries.